2019
DOI: 10.3390/molecules24152768
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Small Oxoacids of Sulfur

Abstract: Oxidation of sulfide to sulfate is known to consist of several steps. Key intermediates in this process are the so-called small oxoacids of sulfur (SOS)—sulfenic HSOH (hydrogen thioperoxide, oxadisulfane, or sulfur hydride hydroxide) and sulfoxylic S(OH)2 acids. Sulfur monoxide can be considered as a dehydrated form of sulfoxylic acid. Although all of these species play an important role in atmospheric chemistry and in organic synthesis, and are also invoked in biochemical processes, they are quite unstable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 101 publications
0
10
0
3
Order By: Relevance
“…We have previously shown that small oxoacids of sulfur (SOS) like HSOH and HOSOH are generated from H 2 S oxidation [21], and thus are likely metabolites of H 2 S in vivo [22]. Here we suggest they are key to the formation of persulfides in the reaction of GSNO and H 2 S. The SOS species demonstrate reactivity and selectivity distinct from polysulfides and thus may function as independent H 2 S-derived signaling agents with unique biological effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that small oxoacids of sulfur (SOS) like HSOH and HOSOH are generated from H 2 S oxidation [21], and thus are likely metabolites of H 2 S in vivo [22]. Here we suggest they are key to the formation of persulfides in the reaction of GSNO and H 2 S. The SOS species demonstrate reactivity and selectivity distinct from polysulfides and thus may function as independent H 2 S-derived signaling agents with unique biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Polysulfides and polysulfide oxides are generated by outer-sphere oxidation of H 2 S with biologically relevant oxidants such as metmyoglobin, hydroxycobalamin and MP-11 (a heme-adduct fragment of cytochrome c) through the initial generation of small oxoacids of sulfur and SOS [21,22]. We proposed that small oxoacids of sulfur, SOS, such as HSOH and HOSOH may be biologically relevant precursors to sulfur-concatenated species through condensation reactions with thiols.…”
Section: Introductionmentioning
confidence: 99%
“…Besides RSS with S-S bonds, hydrogen sulfide can form other reactive species that contain sulfur-oxygen bonds [67][68][69]. Key intermediates in the oxidation of sulfide to sulfate are the so-called small oxoacids of sulfur (SOS)-sulfenic HSOH and sulfoxylic S(OH) 2 acids.…”
Section: Specimen Type [H 2 S] Methods Of Detection Reference (1) Animalmentioning
confidence: 99%
“…The coordination chemistry of sulfur monoxide (SO), which is structurally similar with O 2 , has been of interest since the metal-SO complexes are important intermediates in a series of redox processes in the bioinorganic cycles and catalytic reduction of SO 2 on metal surfaces. [1][2][3][4][5][6] In order to have a better understanding on the roles of SO in these processes, it is necessary to synthesize the corresponding model complexes from which fundamental understanding on how the metal center influences the structure and bonding can be derived. In addition to some compounds with bridging SO ligands, [7][8][9][10] there is a very small number of mononuclear SO complexes, which is mainly due to the instability of sulfur monoxide that makes it difficult to be employed as a precursor.…”
Section: Introductionmentioning
confidence: 99%